Synthesis and Thermomechanical Characterization of Nylon 6/Cu Nanocomposites Produced by an Ultrasound-Assisted Extrusion Method - Rubén Sierra-Ávila; Marissa Pérez-Alvarez; Janett Valdez-Garza; Carlos Alberto Avila-Orta; Enrique Javier Jiménez-Regalado; José M. Mata-Padilla; Enrique Soto-Castruita; Gregorio Cadenas-Pliego (Advances in Materials Science and Engineering)
A nylon 6 nanocomposite with copper nanoparticles processed by ultrasound-assisted extrusion was prepared at concentrations between 0.01 and 0.50 wt.%, and its thermal and mechanical properties were determined. The presence of the crystalline phase α (α1 and α2) in the polymer matrix was confirmed by X-ray diffraction, and the presence of the α2 phase showed a greater increase than the α1 phase as a function of the copper nanoparticle concentration. This process was attributed to secondary crystallization. Furthermore, it was determined that the chemical composition of the nanoparticles is a blend of metallic copper and cupric oxide. The formation of copper nanowires was observed by scanning electron microscopy, and the concentration of 0.10% exhibited the best dispersion in comparison with the other concentrations. The melting temperature of the nanocomposites underwent a slight decrease in comparison with the nylon 6, while thermal stability, crystallization temperature, and crystallinity were increased in relation to the pure polymer. This behavior is attributed to an efficient dispersion of the nanoparticles and to their functionality as crystal nucleation sites. For the 0.10% concentration nanocomposite, higher mechanical properties were obtained; tensile strength increased by 8.9%, and the tensile modulus increased by 25.4%; as a consequence, elongation at break was 62% less than that of the polymer matrix.